L'uomo, il suono e la musica - Alessandro, Bertirotti (Firenze University Press, 2003)
Among the channels of human expression, perhaps the richest of all is music, through which people can express their emotions - in a continuum ranging from joy to grief, from excitement to depression - in a manner that is socially and culturally accessible and acceptable. This book addresses the aspects involved in both producing and listening to music from the point of view of cognitive science. Arguments that might appear hard for non-specialists to understand are addressed in a clear and accessible language. An enthralling itinerary through the various aspects of the human relationship with music that underscores how the long path from the first sounds that man has produced and identified in nature through to the most modern compositions are the result of a process of rationalisation gravitating around the multiform relationship between man, the environment and musical creation.